High dose chemotherapy and autologous hematopoietic stem cell rescue for children with high risk neuroblastoma: Two Case Reports - Nguyen Thi Kim Hoa; Tran Kiem Hao, Chau Van Ha, Phan Canh Duy, Dong Si Sang, Phan Thi Thuy Hoa, Ho Huu Thien, Nguyen Thi My Linh, Pham Nhu Hiep (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2020)
Introduction: High-risk neuroblastoma is a childhood malignancy with a poor prognosis. Gradual improvements in survival have correlated with therapeutic intensity, and the ability to harvest, process, and store autologous hematopoietic stem cells has allowed for dose intensification beyond marrow tolerance. Case: We report two cases diagnosed with high-risk neuroblastoma. The first case involved a 5-year-old male with a large heterogeneous tumor in his left adrenal gland and metastasis in the bone marrow and brain. The second case was a 5-year-old female with a localized tumor in her right kidney and NMYC positive. Both cases were treated with the SIOPEN protocol, starting with 8 courses of RAPID COJECT. After partial response, stem cells were collected, followed by primary tumor resection, high-dose chemotherapy with autologous stem cell rescue, radiation, and retinoic acid treatment. Conclusion: This report is the initial documentation of autologous stem cell transplant for high-risk neuroblastoma. Despite involving only two patients, the results indicated that stem cell transplant was safe and effective. We aim to implement this treatment for more cases of high-risk neuroblastoma and report further findings with a larger cohort.